How Effective Are Federally Mandated Information Disclosures?. Issue 2 (30th August 2016) - Fraas, Arthur G.; Lutter, Randall
Abstract : Government mandates to disclose information are a standard response to problems of asymmetric information. We examine recent major U.S. regulations issued between 2008 and 2013 to identify disclosure mandates and look for quantitative assessments of their effectiveness in improving comprehension. We also reviewed the retrospective regulatory review reports of four federal agencies – prepared pursuant to Executive Orders 13563 and 13579 – for analyses of existing mandates. We find that although mandated disclosures underpin a number of major federal regulatory initiatives, agencies infrequently issue such mandates based on scientifically valid, controlled studies of the improvements in comprehension from such disclosure. We also conduct four case studies drawn from the relatively few instances where federal agencies have evaluated improvements in comprehension, to identify current best practices. Finally, we recommend reforms to improve federally mandated information disclosure.